SPIRITUAL INTELLIGENCE AS A PREDICTOR OF SELF-EFFICACY: A CONCEPTUAL FRAMEWORK - Rastogi, Pallavi; Chandra, Ritu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Spiritual intelligence (SI) has gained increasing attention in psychology and education as a vital factor influencing personal and profession success. Self-efficacy, a key component of social cognitive theory, determines individuals' confidence in their ability to accomplish tasks and achieve goals. This paper explores the conceptual framework that links spiritual intelligence and self-efficacy. It examines the theoretical underpinnings of both constructs, their interrelation, and how spiritual intelligence can serve as a predictor of self-efficacy. The paper also discusses potential mechanisms through which spiritual intelligence enhances self-efficacy, including resilience, intrinsic motivation, and self-awareness. Implications for education, workplace performance, and mental well-being are also explored.